Ontology development for Islamic supplications - Mohd Tawil, Fatimah; Othman, Roslina (IIUM Press, International Islamic University Malaysia, 2017)
This book presented the ontology development for Do’a and Zikr al-Mā’thur for counselling. The developed ontology is used as a mechanism to ease the way of finding the right Do’a and Zikr al-Mā’thur with its corresponding counselling cases and functions as a dynamic knowledge base platform for a semantic web. The ontology was assessed and evaluated with the proper standard of assessment during the development phase and after the completion of ontology development phase.